Pengaruh Model Teams Games Tournament (TGT) untuk Menciptakan Pembelajaran Efektif dan Menyenangkan - Khofifatul Mabruroh; Moh. Vito Miftakhul Munif (AJER: Advanced Journal of Education and Religion, 2026)
This study aims to investigate the effect of the Teams Games Tournament (TGT) learning model in creating effective and enjoyable learning in Grade IV at MI Ma’arif NU Pucuk for the 2024/2025 academic year. The background of this research is the low level of student engagement and enthusiasm in the learning process due to monotonous conventional teaching methods. This study employs a quantitative approach with a pre-experimental one-group pretest-posttest design. The research subjects consisted of 32 students. Data collection techniques included tests (pretest and posttest) to measure learning effectiveness, and questionnaires to determine the level of students’ enjoyment during the learning process. The data analysis techniques used were descriptive statistics and inferential statistics in the form of a Paired Sample T-Test. The results showed that the average pretest score of 64.34 increased to 88.25 in the posttest. The results of the Paired Sample T-Test showed a significance value of 0.000 < 0.05, indicating a significant difference between the pretest and posttest scores. This proves that the TGT model is effective in improving student learning outcomes. In addition, the questionnaire results showed that 62.5% of students considered the learning to be very enjoyable, and 37.5% found it enjoyable. No students felt that the learning was less or not enjoyable. Therefore, the TGT model has been proven to have a positive impact in creating effective and enjoyable learning.